The inequitable delivery of vaccines in the COVID-19 pandemic - Sood, Tushar; Mehta, Vikita (The Meducator, 2022)
Vaccines have been shown to be effective at curbing infection rates and significantly lowering the risk of hospitalization and ICU admission. During the most recent outbreak of the Omicron variant, COVID-19 vaccines, especially after three doses, have continued to offer strong protection in minimizing hospitalization and ICU admission. The most effective protection is achieved through widespread population vaccine uptake. While there has been strong uptake in many high-income countries —including Canada, where 78.7% of the total population is fully vaccinated with at least two doses— limited supply and access in many low- and middle-income countries (LMICs) has hindered similar populationlevel protection. For example, only 10% of people in African countries are fully vaccinated against COVID-19 (received at least two doses) and approximately 1.2 billion people in African countries have not received a single dose. Given the importance of an effective global response to the COVID-19 pandemic, this article explores the implications of the key legal, economic, and sociocultural factors, as well as features of the vaccine roll-out that are driving vaccine inequity. Potential options for policymakers to make vaccine access more equitable domestically and internationally are also suggested in this review.